2014
DOI: 10.1007/s00203-014-0958-2
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of plantaricin Y, a novel bacteriocin produced by Lactobacillus plantarum 510

Abstract: Lactobacillus plantarum 510, previously isolated from a koshu vineyard in Japan, was found to produce a bacteriocin-like inhibitory substance which was purified and characterized. Mass spectrometry analysis showed that the mass of this bacteriocin is 4,296.65 Da. A partial sequence, NH2- SSSLLNTAWRKFG, was obtained by N-terminal amino acid sequence analysis. A BLAST search revealed that this is a unique sequence; this peptide is thus a novel bacteriocin produced by Lactobacillus plantarum 510 and was termed pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…The production of bacteriocins has been described for several strains of lactobacilli in 350 weight-gain and weight-loss associated genomes [126][127][128][129][130][131][132]. However, weight gain-associated 351 genomes were found to encode more bacteriocins than weight loss-associated genomes [88].…”
mentioning
confidence: 98%
“…The production of bacteriocins has been described for several strains of lactobacilli in 350 weight-gain and weight-loss associated genomes [126][127][128][129][130][131][132]. However, weight gain-associated 351 genomes were found to encode more bacteriocins than weight loss-associated genomes [88].…”
mentioning
confidence: 98%
“…Plantaricin LD1 produced by food isolate of Lactobacillus plantarum LD1 inhibited not only related strains but also other gram-positive and gram-negative bacteria such as S. aureus, P. aeruginosa, S. typhi as described by Gupta and Tiwari (2014). Plantaricin Y produced by L. plantarum 510 reported by Chen et al (2014) showed strong inhibitory activity against L. monocytogenes BCRC 14845.…”
Section: Resultsmentioning
confidence: 96%
“…They are completely active usually because of the synergistic action of the two peptides, while each peptide alone has less or no activity. In all previous studies, the optimal combination ratio of the two peptides is about 1:1 (Chen et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
“…The harvested cell-free supernatant was desalted and purified using a C 18 cartridge (Sep-Pak C 18 ; Waters, Milford, MA, USA) following Chen et al (17). Antimicrobial activity of the peptide fractions was tested using agar-spot diffusion assay (18).…”
Section: Bacteriocin Purificationmentioning
confidence: 99%